2005
DOI: 10.1529/biophysj.104.058842
|View full text |Cite
|
Sign up to set email alerts
|

Disorder Influence on Linear Dichroism Analyses of Smectic Phases

Abstract: Linear dichroism, the unequal absorption of parallel and perpendicular linear polarized light, is often used to determine the anisotropic ordering of rodlike polymers in a smectic phase, such as helices in a lipid bilayer. It is a measure of two properties of the sample: 1), orientation of the chromophore transition dipole moment (TDM) and 2), disorder. Since it is the orientation of the chromophore TDM that is needed for high resolution structural studies, it is imperative to either deconvolve sample disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
(40 reference statements)
3
13
0
Order By: Relevance
“…One limitation complicating the use of polarized IR spectroscopy on oriented samples to derive structural information is the sample disorder, which results from the fact that without further corrections the experimentally obtained order parameter is defined with respect to the window normal and not with respect to the membrane normal. As a result, the experimental order parameter needs to be corrected for the second-order parameter of the membrane normal with respect to the window normal, known as the mosaic spread . In addition, the order parameter can only be converted into an angle value by ignoring potential heterogeneities (e.g., mixture of conformations) as well as dynamical aspects (e.g., thermal fluctuations in the angle).…”
Section: Interactions and Properties That Shape Ir Bandssupporting
confidence: 80%
“…One limitation complicating the use of polarized IR spectroscopy on oriented samples to derive structural information is the sample disorder, which results from the fact that without further corrections the experimentally obtained order parameter is defined with respect to the window normal and not with respect to the membrane normal. As a result, the experimental order parameter needs to be corrected for the second-order parameter of the membrane normal with respect to the window normal, known as the mosaic spread . In addition, the order parameter can only be converted into an angle value by ignoring potential heterogeneities (e.g., mixture of conformations) as well as dynamical aspects (e.g., thermal fluctuations in the angle).…”
Section: Interactions and Properties That Shape Ir Bandssupporting
confidence: 80%
“…Thus, henceforth for simplicity we shall refer to our measurements as yielding the angle between the bilayer normal and the C=O bond. The precise procedures for deriving the aforementioned angle is according to protocols that we have established in the past (Manor et al, 2005) and are outlined in the Supplemental Information Methods Section. Briefly, the process consists of: (i) reconstituting the labelled channels in hydrated vesicles, (ii) removal of bulk solvent whilst depositing the membranes on a solid support to create aligned bilayers, (iii) measuring the dichroism using ATR-FTIR spectroscopy, (iv) assessing the bilayer disorder by X-ray scattering, and finally (v) converting the measured dichroisms to the angles of the carbonyl groups with respect to the membrane normal.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the ATR-FTIR spectroscopy and the X-ray Scattering bilayer mosaicity estimation were undertaken as described elsewhere (Manor et al, 2005; Torres et al, 2000b), and specified in detail in the Supplemental Information Section.…”
Section: Methodsmentioning
confidence: 99%
“…Reported S L values for DMPC in the literature are in the range of 0.5-0.8 (28), which is similar to the observed S L of 0.7. Explicit analysis of sample disorder in similar DMPC͞peptide samples concluded that sample disorder was not significant (44), but this analysis may not be directly comparable. In any case, our data would not be compatible with a helix perpendicular to the membrane.…”
Section: Ir Spectroscopy In Lipid Bilayersmentioning
confidence: 94%